Telegram, 1932 May 20, Harbour Grace, Nfld., to G.P. Putnam, New York - Parkes (Purdue University Libraries, Archives and Special Collections, 1932)
“Parkes” telegram to George Palmer Putnam from Newfoundland, “A.E. took off 7:12 NFLD D.S.T. Perfect performance all wires and reports received,” May 20, 1932